Resistive pulse sensing of pre-nucleation activities during single-entity lysozyme crystallization on single nanopipettes - Yusuff Balogun; Ruoyu Yang; Gangli Wang (Sensors and Actuators Reports)
The formation of cluster aggregates in a (super)saturated solution prior to protein nucleation is crucial to overcoming the thermodynamic energy barrier which enables further growth of single crystals. This process is important for single crystal growth, separation and energy conversion among other important applications. For structural determination of biomacromolecules, neutron crystallography holds unique advantages in resolving hydrogen/proton over other structure determination techniques but faces technical obstacles in requiring large high-quality single crystals and preferentially hydrogen-deuterium exchanges. Herein, we explore protein nucleation in heavy water (D2O) via nanopore-based resistive pulse sensing, with lysozyme as prototype. By controlling localized supersaturation and phase transition at a nanopore through adjusting the potential waveform, a single protein crystal can be grown. Our focus is on understanding the translocation and/or transformation of protein aggregates through nanopores prior to the irreversible nucleation. As expected, higher protein concentrations tend to facilitate nucleation and growth of a single protein crystal with higher supersaturation, consistent with bulk experiments. At lower protein concentrations, individual current spikes are resolved as characteristic single-entity events in resistive pulse sensing. Those transient events are potential-dependent characterized by the peak amplitude, duration and area/charges. Statistical analysis reveals both translocation of protein oligomers and their transformation or further aggregation. This study represents the first step toward elucidating valuable insights into the dynamics of protein translocation and aggregation in heavy water and demonstrates the potential of using nanopores in the detection and characterization of dynamic phase transitions at single-event levels.